Geo-strategic intervention and its consequences in the Horn of Africa - Bereketeab, Redie (2014)
This article seeks to examine the role geo-strategic driven interest politics plays in security, stability, development and democratisation in the Horn of Africa (HOA). It aims to interrogate the various external interventions in the region with the aim of enhancing geostrategic interest of great powers. The most notorious geo-strategic driven intervention in postcolonial time in the region was the Cold War rivalry of the superpowers that transformed the region into playground of bipolar strife. The end of Cold War brought a brief respite in the geostrategic driven intervention in the region. The US global war on terror and the war against piracy offshores of Somalia brought again the politics of geo-strategic intervention to the region. What are the consequences of the politics of geo-strategic interest to the region? This article examines the consequences of the geo-strategic interest driven intervention to security, stability, development and democratisation in the HOA.